2014
DOI: 10.1002/2014ja020228
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lived plasmaspheric drainage plumes: Where does the plasma come from?

Abstract: Long-lived (weeks) plasmaspheric drainage plumes are explored. The long-lived plumes occur during long-lived high-speed-stream-driven storms. Spacecraft in geosynchronous orbit see the plumes as dense plasmaspheric plasma advecting sunward toward the dayside magnetopause. The older plumes have the same densities and local time widths as younger plumes, and like younger plumes they are lumpy in density and they reside in a spatial gap in the electron plasma sheet (in sort of a drainage corridor). Magnetospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 145 publications
(240 reference statements)
1
43
0
Order By: Relevance
“…In contrast Borovsky et al . [] find what appears to be drainage plumes persisting for many days during times of elevated Kp . The initial drainage of the outer plasmasphere is found to take place over 1.5–2 days and is sometimes followed by sustained, narrow‐MLT plume‐like high densities for as long as 11 or more days.…”
Section: State Of Modeled Refillingmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast Borovsky et al . [] find what appears to be drainage plumes persisting for many days during times of elevated Kp . The initial drainage of the outer plasmasphere is found to take place over 1.5–2 days and is sometimes followed by sustained, narrow‐MLT plume‐like high densities for as long as 11 or more days.…”
Section: State Of Modeled Refillingmentioning
confidence: 90%
“…Other possible sources for this plasma are suggested by Borovsky et al . [] to be substorm disruption of the remaining interior plasmasphere, velocity‐shear instability, and the high‐latitude tongue of ionization. Notably, Krall and Huba [] find refilling within a factor of 2 of observation at L = 2 and 3 using SAMI3, but falling below observed refilling by a factor of 5 at L = 5.…”
Section: State Of Modeled Refillingmentioning
confidence: 99%
“…Plasmaspheric plumes are found to be favorable for enhancing pitch angle scattering of radiation belt electrons, thus leading to electron precipitation into the upper atmosphere (Borovsky et al, 2014;Summers et al, 2008;Zhang et al, 2018). Borovsky and Steinberg (2006) found that relativistic electron dropouts at geosynchronous orbit often coincided with the presence of plasmaspheric plumes, suggesting the potential loss of energetic electrons due to interactions with the enhanced plasma waves in plumes.…”
Section: Citationmentioning
confidence: 99%
“…They are often long-lived, being observed for days at geosynchronous orbit (e.g., Borovsky et al, 2014), are usually narrow in longitude and appear at all longitudes/MLT (e.g., Moldwin et al, 1994), can have significant structure (e.g., Moldwin et al, 1994Moldwin et al, , 1995Darrouzet, et al, 2008;Sibanda et al, 2012), and can exist at any level of geomagnetic activity -though they are primarily associated with enhancements in activity (though not necessarily storms) (Moldwin et al, 2004). Figure 3 shows the occurrence of plumes observed by CRRES as a function of the Kp index compared to the distribution of Kp observed during the CRRES mission lifetime.…”
Section: Plasmaspheric Plumementioning
confidence: 99%
“…Through the formation and evolution of the different plumes, they impact wave generation and wave-particle interactions (e.g., Summers et al, 2008;Chen et al, 2012;Halford et al, 2015), particle precipitation (Spasojević and Fuselier, 2009;Yuan et al, 2011Yuan et al, , 2013, ion outflow (e.g., Zeng and Horowitz, 2008;Tu et al, 2007), local-time asymmetries in ULF wave field-line resonance (FLR) signatures (e.g., Archer et al, 2015;Ellington et al, 2016), satellite communication and navigation systems (Ledvina et al, 2004;Basu et al, 2005;Datta-Barua et al, 2014), and even the coupling efficiency of the solar wind to the magnetosphere (Borovsky and Denton, 2006;Borovsky et al, 2013;Ouellette et al, 2016;Fuselier et al, 2016). Though we now have a new appreciation and understanding of plumes, there are still many unanswered questions on their formation (e.g., Kelley et al, 2004;Horvath and Lovell, 2011;Zou et al, 2013Zou et al, , 2014Borovsky et al, 2014) and impact on global magnetospheric dynamics McFadden et al 2008;Walsh et al, 2014Walsh et al, , 2015. We propose that the shift in our conceptual understanding of the plasmasphere (Carpenter and Lemaire, 2004) now needs to extend down to the ionosphere and include a framework that connects the threedimensional plasmasphere-ionosphere-magnetosphere system.…”
Section: Introductionmentioning
confidence: 99%